Probiotic Potential of Yeasts Isolated from Fermented Beverages: Assessment of Antagonistic Strategies Against Salmonella enterica Serovar Enteritidis - Vergara Alvarez, Silvia Cristina (2024)
Global concern about pathogenic resistance to antibiotics is prompting interest in probioticsas a strategy to prevent or inhibit infections. Fermented beverages are promising sources of probiotic yeasts. This study aimed to evaluate the antagonistic effects of Kluyveromyces marxianus, Wickerhamomyces anomalus, and Pichia manshurica strains from kefir and wine against Salmonella enterica serovar Enteritidis in intestinal epithelial cells. The ability of these yeasts to adhere to Caco-2/TC-7 cells was evaluated, as well as their influence on the ability of Salmonella to associate and invade these cells. The behavior of the pathogen was analyzed by (a) incubation of enterocytes with yeast before adding Salmonella, (b) co-incubation of Salmonella with yeast before contact with the enterocytes, and (c) incubation of Salmonella with yeast metabolites before contact with enterocytes. All yeast strains demonstrated adherence to Caco-2/TC-7 cells (33–100%) and effectively inhibited Salmonella invasion.Among the treatments, co-culture showed the greatest effect, reducing Salmonella association andinvasion by more than 50%. Additionally, these yeasts modulated the epithelial immune response,significantly decreasing CCL20-driven luminescence by 60–81% (p < 0.0001). These results highlight the potential of yeasts from fermented beverages as probiotics to counteract Salmonella infections, offering a promising alternative in the fight against antibiotic resistance.